2021
DOI: 10.1155/2021/8820082
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Reversible Watermarking Techniques of Echocardiography

Abstract: In critical domains such as medical and military, reversible watermarking (RW) has been used. In the medical domain, different modalities are used to store patient information. The current study focuses on the application of RW in echocardiography data. Mostly, RW is applied to protect patient data without affecting the quality of the decoded image. The RW methods are benchmarked as per imperceptibility, robustness, and payload. The survey presents a comparison of state-of-the-art RW techniques. The impercepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…First, use the method in Section 3.2 to obtain the same chaotic sequence X(i), and similarly, use it to construct the binary matrix K(i, j). Finally, the extracted watermark EW ′ (i, j) is decrypted according to equation (8), and the unencrypted watermark W ′ (i, j) is obtained. Figure 10 shows this process.…”
Section: Watermark Decryptionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, use the method in Section 3.2 to obtain the same chaotic sequence X(i), and similarly, use it to construct the binary matrix K(i, j). Finally, the extracted watermark EW ′ (i, j) is decrypted according to equation (8), and the unencrypted watermark W ′ (i, j) is obtained. Figure 10 shows this process.…”
Section: Watermark Decryptionmentioning
confidence: 99%
“…Most of the traditional medical systems have turned to electronic medical systems [7]. Patient data such as current and past disease information, medical images, and drug information can be stored in electronic medical records (EMR) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many algorithms have been proposed in the literature and often rely on robust random key generation [13]. A method of generating a secure key with reduced latency and based on the cardiogram in encryption [14] has been proposed. An improved method was proposed by [15] to heal the medical image using Fibonacci, which had the effect of scattering and hiding the information of the medical image [16].…”
Section: Related Workmentioning
confidence: 99%
“…The authors also suggested that hardware-based watermarking can be used to support real-time applications. Finally, they recommended that the hybridization of two or more watermarking techniques will enhance watermarking performance; however, this will also increase the computational complexity.Ghafoor et al[101] provided an overview of reversible watermarking in echocardiography applications. Reversible watermarking is an efficient tool which has uses in critical domains such as military and medical applications.…”
mentioning
confidence: 99%